Hypoglycemic effect of ethanolic extract of hedychium coronarium linn. rhizome in alloxan induced diabetes in rat model (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
PurposeTo study the hypoglycemic effect of ethanolic extract of Hedychium  coronarium Linn. rhizome in alloxan  induced  diabetes  in  rat  model.MethodsThe preliminary photochemical studies were carried out on the crude extract and the various chemical constituents present in the crude extract were evaluated. Acute toxicity studies as per OECD-23 guidelines to determine the safety doses of the root extract were carried out on male wistar strain of Albino rats. The various factors such as body weight, feed intake, blood glucose and serum insulin were regularly studied and evaluated.ResultsThe hypoglycemic effect of ethanolic extract of Hedychium coronarium Linn. rhizome was studied on the various factors such as body weight, blood glucose levels of the alloxan induced diabetic rat model.ConclusionIn present study administration of Hedychium coronarium Linn. rhizome extract produced a significant reduction in blood glucose, serum insulin, serum catalase and haemoglobin in alloxan induced rats. However, it seems promising that if this data will be validated in the future clinical trials, Hedychium coronarium rhizome extract may offer an alternative treatment for diabetes.